MEASUREMENTS OF IRON CONCENTRATION IN KAOLINITES CONSIDERING DISORDER BROADENING OF EPR LINES - Gaite J.M.; Muller F.; Jemai S. (My University, 2003)
Only one part of the EPR lines of a kaolinite spectrum of structural Fe3+ is clearly observable because of the overlapping of other lines with other spectra. For this reason, to determine the structural Fe3+ concentration we used the line near g=9, although it is not intense. A standard is needed: powders of ZnS containing given concentrations of Mn2+ (isoelectronic to Fe3+) were used for this purpose. Using the simulations of the EPR spectra, the concentration (number of Fe3+ per Al3+) is determined; it is in the range 10−5 to 10−4 for our samples. Considering that the crystal-field disorder around Fe3+ is responsible for line broadening, we looked for a possible effect of the broadening on the intensity of the EPR spectra. This effect is taken as a distribution of the parameter λ=B 22/B 20. The influence of the parameter λ and its statistical distribution on the position, shape, width and intensity of the EPR line has been calculated using simulation procedures. The correction due to the disorder on the calculated concentration is of the same order of magnitude as the precision measurement. This method can be applied for other kaolinites by comparing the area of their g=9 lines with known ones.
Keywords: Kaolinite; EPR; Fe3+